PROTESTANT LORD IN JAMES VI'S SCOTLAND : george keith, fifth earl marischal (1554-1623). - KERR-PETERSON, MILES (St Andrews studies in Scottish history series, 2019)
George Keith, fifth Earl Marischal, is an outstanding example of long-term successful Protestant Lordship in the reign of James VI. The founder of Marischal College in Aberdeen and the towns of Peterhead and Stonehaven, reputed to be the richest earl in Scotland, Marischal and his kindred were witness to a Scotland reeling from the consequences of the Protestant Reformation and coming to terms with their ambitious new king, who would be whisked away to England in 1603. This book explores Marischal's political struggles in the north east and at court, and his strategies in managing the kindred throughout these storms. He was economically active in estate improvement, shipping and finance, and was prominent in regional activities such as feuding and upholding local justice. An exploration of the Keiths' interaction with the Protestant Kirk redresses the notion of the "Conservative North East" of Scotland, but also reveals the conflict between earthly lordship and godly reform. Marischal, King James' "Little Fat Pork", is thus a perfect window into noble society, religion and politics in Jacobean Scotland